The Development of Librarianship in Turkey - Doğan Atılgan (Türk Kütüphaneciliği)
Librarianship in Turkey had become a concern along with the foundation of the Republic. The important steps concerning librarianship were undertaken in the same era, too. Education for librarianship was first started with short courses and continued with an institute. Later, departments of librarianship were established at universities. Today, graduates of such departments work in various kinds of libraries with differing names and functions in Turkey. This paper aims to introduce the Turkish librarianship to the attendees of the IFLA General Council and Conference that is to take place in Turkey in August 1995.